Seroepidemiology of pertussis immunity in five provinces of China: A population-based, cross-sectional study - Zhujiazi Zhang; Qing Wang; Qi Zhu; Shuang Bai; Yang Liu; Jia Ren; Xin Xu; Jiangwen Qu; Jingbin Pan; Li Lu; Luodan Suo; Xiaodong Sun; et al. (Taylor & Francis Group, 2024)
This study aimed to evaluate the seroprevalence of Bordetella pertussis and persistence of antibodies following vaccination. We recruited 6060 healthy subjects from five provinces of China during 2017-2018. Serum IgG antibodies against pertussis toxin (anti-PT IgG) and filamentous hemagglutinin (anti-FHA IgG), and serum IgA antibodies against pertussis toxin (anti-PT IgA) were measured by ELISA. Geometric mean concentration (GMC), seropositivity rate, and recent infection rate were calculated. Among 0-6 years-olds, the anti-PT IgG, anti-PT IgA, and anti-FHA IgG GMCs were 6.4 IU/ml (95% CI 6.1-6.8), 2.8 IU/ml (95% CI 2.7-2.8), and 13.3 IU/ml (95% CI 12.4-14.2), respectively. The anti-PT IgG GMC increased in accordance with the primary vaccination series (4-6 months) and the toddler booster (18-24 months), but declined thereafter through to age 5 years [4.7 IU/ml (95% CI 4.2-5.4)]. The seropositivity rate of pertussis in >6 year-olds was 9.0% (95% CI 8.1-9.9) and the recent infection rate was 3.3% (95% CI, 2.7-3.8). Recent infection rate began to increase from 6 years of age, with peaks at 9, 20, 40, and ≥60 years of age. The anti-PT IgG GMCs of children aged 0-6 years who were vaccinated with DTaP, DTaP-IPV//PRP～T, and DTaP-Hib were 5.9 IU/ml (95% CI 5.6-6.3), 20.7 IU/ml (95% CI 15.6-27.8), and 11.7 IU/ml (95% CI 7.5-18.1) (p < .001), respectively (p < .001). Pertussis vaccination improves anti-PT IgG levels, however these wane soon after vaccination. Sero-estimated recent infection rates appear to increase from school age into adolescence and adulthood. Pertussis vaccine boosters should be considered in these age groups.